The Impact Of Good Corporate Governance To Manufacturing Firm’s Profitability And Firm’s Value - Johanes Sumarno; Sendy Widjaja; Subandriah Subandriah (Signifikan: Jurnal Ilmu Ekonomi, 2016)
This paper studied the behavior of management toward the implementation of Good Corporate Governance in Indonesia to determine whether it has any influence towards profitability and its implication to the Manufacturing Firms’ value publicly listed in Indonesian Stock Exchange. There were 41 corporations who met the criteria of the survey. The data were analyzed using Panel Regression with fixed effects Model. The empirical findings show that the implementation of Corporate Governance in Indonesia has a positive, significant and direct impact toward firms’ profitability and firms’ value. Corporate Governance principles based on OECD principles that have positive and significant impact to both profitability and Firms’ Valueis Rights of Shareholders, Role of Stakeholders, Responsibilities of the Board Commissioners and Board of Directors. The principles that have significance and negative impact towards corporate profitability and value, are: Equitable treatment of shareholders and Disclosure and Transparencies. The most significant principle influencing profitability and firms’ value is Disclosure and Transparencies. Profitability plays a greater role in influencing Manufacturing Firms’ value in Indonesia. DOI: 10.15408/sjie.v5i2.3542